Influence of baking and frying conditions on acrylamide formation in various prepared bakery, snack, and fried products - Ahmad, Muhammad Mushtaq; Qureshi, Tahir Mahmood; Mushtaq, Maham; Aqib, Amjad Islam; Mushtaq, Umair; Ibrahim, Salam A.; Rehman, Abdul; Iqbal, Muhammad Waheed; Imran, Tabish; Siddiqui, Shahida Anusha; Javed, Anjum; Shamim, Sadaf; et al. (Frontiers in Nutrition, 2022)
The core objective of the present study was to evaluate the influence of baking/frying times and temperatures on the formation of acrylamide in bakery, snack and fried products such as biscuits, muffins, pizza and cakes, samosa, paratha rolls, nuggets and potato cutlets during baking/frying at different time and temperature conditions. First of all, the raw material, especially flour was tested for its proximate composition and rheological characteristics. The quantification of acrylamide produced during processing of different products was carried out through HPLC method. Sensory evaluation of these food samples was also carried out to find out the acceptability differences. The raw material was found to have good rheological properties and proximate composition. The results revealed that different time and temperature regime had influence on the formation of acrylamide in those products. Among the bakery products, the highest concentrations of acrylamide were observed in biscuits (126.52 µg/kg) followed by muffin (84.24 µg/kg), cake (71.21 µg/kg) and pizza (62.42µg/kg). The higher contents of acrylamide were found in paratha roll (165.92 µg/kg) compared to samosa (100.43 µg/kg) whereas among snacks, potato cutlets (135.71 µg/kg) showed higher concentrations than nuggets (43.04 µg/kg). It was observed that baking or frying of all the investigated products at higher temperature produced slightly more acrylamide concentrations. The prepared products in the present study were also accepted sensorially by the panel of judges. So, it was concluded that baking or frying at higher temperature resulted in higher concentrations of acrylamide compounds in different products studied in the present study.